Cross-cultural validity and measurement invariance of the Organizational Stressor Indicator for Sport Performers (OSI-SP) across three countries - Arnold, R.; Ponnusamy, V.; Zhang, C.-Q.; Gucciardi, D. FR. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Organizational stressors are a universal phenomenon which can be particularly prevalent and problematic for sport performers. In view of their global existence, it is surprising that no studies have examined cross-cultural differences in organizational stressors. One explanation for this is that the Organizational Stressor Indicator for Sport Performers (OSI-SP; Arnold, Fletcher, & Daniels, 2013), which can comprehensively measure the organizational pressures that sport performers have encountered, has not yet been translated from English into any other languages nor scrutinized cross-culturally. The first purpose of this study, therefore, was to examine the cross-cultural validity of the OSI-SP. In addition, the study aimed to test the equivalence of the OSI-SP's factor structure across cultures. British (n = 379), Chinese (n = 335), and Malaysian (n = 444) sport performers completed the OSI-SP. Confirmatory factor analyses confirmed the cross-cultural validity of the factorial model for the British and Malaysian samples; however, the overall model fit for the Chinese data did not meet all guideline values. Support was provided for the equality of factor loadings, variances, and covariances on the OSI-SP across the British and Malaysian cultures. These findings advance knowledge and understanding on the cross-cultural existence, conceptualization, and operationalization of organizational stressors.